The failure of the International Criminal Court in Africa : decolonising global justice - Benyera, Everisto (London ; New York : Routledge, 2022)
"This book investigates the relationship between the International Criminal Court and Africa, asking why and how the international criminal justice system has so far largely failed the victims of atrocities in Africa. The book explores how the Court degenerated from a very promising multilateral institution to being an instrumentalized, politicized, weaponized institution which ended up with the victims being the greatest losers. Instead of looking at the International Criminal Court as a recent alternative to the prevailing paradigm, that book argues that it is a manifestation of the same world order that was established by the Reconquista in 1492. Written from a decolonial perspective, the book particularly draws on evidence from Zimbabwe in order to demonstrate how the International Criminal Court is failing the victims of the four crimes that falls under its jurisdiction. Drawing on the perspectives of victims in particular, this book highlights the damage caused within Africa by the international justice system and argues for a decolonial concept of justice. It will be of interest to researchers from across African politics, international relations, law, and criminal justice"--
Self-writing as restitutive justice in Africa : an introduction -- The international justice system as a justice problem for Africa -- The ICC and prosecutorial obsession -- Is the ICC unfairly targeting Africa -- Can (post)colonial states deliver international criminal justice -- The ICC and international criminal justice in Zimbabwe -- The immunity of state officials and the complexities of prosecuting African leaders at the ICC -- Rethinking and reconstituting the international criminal justice system : towards a cure which heals the patient.
OCLC-licensed vendor bibliographic record.
Keywords: International Criminal Court; International criminal courts -- Africa; International crimes -- Africa; Criminal justice, Administration of -- Africa -- International cooperation; Decolonization -- Africa